Safranal Treatment Improves Hyperglycemia, Hyperlipidemia and Oxidative Stress in Streptozotocin-Induced Diabetic Rats - Saeed Samarghandian; Abasalt Borji; Mohammad Bagher Delkhosh; Fariborz Samini (Frontiers Media S.A., 2013)
Purpose. Clinical research has confirmed the efficacy of several plant extracts in the modulation of oxidative stress associated with diabetes mellitus. Findings indicate that safranal has antioxidant properties. The aim of the present study was the evaluation of possible protective effects of safranal against oxidative damage in diabetic rats. Methods. In this study, the rats were divided into the following groups of 8 animals each: control, untreated diabetic, three safranal (0.25, 0.50, 0.75 mg/kg/day)-treated diabetic groups. Diabetes was induced by streptozotocin (STZ) in rats. STZ was injected intraperitoneally at a single dose of 60 mg/kg for diabetes induction. Safranal (intraperitoneal injection) was administered 3 days after STZ administration; these injections were continued to the end of the study (4 weeks). At the end of the 4-week period, blood was drawn for biochemical assays. In order to determine the changes of cellular antioxidant defense systems, antioxidant enzymes including glutathione peroxidase (GSHPx), superoxide dismutase (SOD) and catalase (CAT) activities were measured in serum. Moreover we also measured serum nitric oxide (NO) and serum malondialdehyde (MDA) levels, a marker of lipid peroxidation.  Results. STZ-induced diabetes caused an elevation (p < 0.001) of blood glucose, MDA, NO, total lipids, triglycerides and cholesterol, with reduction of GSH level and CAT and SOD activities. The results indicated that the significant elevation in the blood glucose, MDA, NO, total lipids, triglycerides, cholesterol and reduction of glutathione level and CAT and SOD activity were ameliorated in the safranal-treated diabetic groups compared with the untreated groups, in a dose dependent manner (p < 0.05, p<0.01, p < 0.001). Conclusion. These results suggest that safranal has antioxidant properties and improves chemically-induced diabetes and its complications by modulation of oxidative stress. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.